2018
DOI: 10.1038/s41598-018-26671-3
|View full text |Cite
|
Sign up to set email alerts
|

Amblyopia, Strabismus and Refractive Errors in Congenital Ptosis: a systematic review and meta-analysis

Abstract: Congenital ptosis may be associated with abnormalities of visual development and function, including amblyopia, strabismus and refractive errors. However, the prevalence estimates of these abnormalities vary widely. We performed a systematic review and meta-analysis to estimate the prevalence of amblyopia, strabismus and refractive errors in congenital ptosis. Cochrane, Pubmed, Medline, Embase, and Web of Science were searched by July 2017. We used random/fixed effects models based on a proportion approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…Associated strabismus was found in 8% of the patients. Higher prevalence (19.6%) of strabismus is reported in recent meta-analysis 13 . No patient had any systemic association or family history for ptosis in our study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Associated strabismus was found in 8% of the patients. Higher prevalence (19.6%) of strabismus is reported in recent meta-analysis 13 . No patient had any systemic association or family history for ptosis in our study.…”
Section: Discussionmentioning
confidence: 78%
“…In a meta-analysis by Yijie et al, the prevalence of amblyopia in congenital ptosis ranged from 18.5-27.8% 13 . In our study 28% patients had associated amblyopia with congenital ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of refractive error and strabismus are one of the two most common causative factors in the development of amblyopia. Zhu et al, concluded that uncorrected refractive error is more important factor than deviation [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of a recent report on refractive error in congenital ptosis, which found a high incidence of anisometropia; however, that study mainly focused on the prevalence of myopic anisometropia [ 2 ]. A recent meta-analysis of patients with congenital ptosis showed that among various types of refractive error, myopia was the most prevalent (30.2%), followed by anisometropia (17.3%) [ 7 ]. Differences among reports in the prevalence of refractive errors may be due to variations in patient age at the time of cycloplegic refraction measurement.…”
Section: Discussionmentioning
confidence: 99%